Life Cycle Assessment of Water HeatingSystems Used in Health Clubs - Ali M. Abbas (My University, 2015)
Commercial water heating systems are known for their high-energy consumption and high environmental effects. This study compares between three heating systems suggested for an average health club in the city of Nablus, Palestine. The study took into consideration the daily hot water needs for the health club. Three water heating systems are considered which are electric boiler, heat pump, and gas fired boiler. The reason behind choosing the above mentioned systems is its availability and feasibility in local market. A cradle to grave boundary limits has been adopted in this research, and the functional unit is 8 m3/day at 43 °C. However, the Center of Environmental Science of Leiden University (CML) life cycle impact assessment (LCIA) method has been implemented due to its reliability and accuracy in such applications. It classifies the environmental effects into ten main clusters. Moreover, the study includes life cycle costing (LCC) analysis by using the present worth value and assuming the minimum attractive rate of return to be 10% per year. The study reveals that the heat pump system is the least energy consumptive during its life cycle, then the gas boiler, and the electric boiler is relatively the worst. However, from economic point of view, the cost of operating such systems consists mainly of its initial cost. Results show that heat pump system has the lowest LCC with 102,684 USD, then the gas fired boiler with 167,428 USD, and the worst system from LCC point of view is the electric boiler with 246,433 USD. In contrast, CML method results show that the gas boiler is considered the most environmental friendly; the heat pump comes second, followed by the electric boiler. Finally, two scenarios of sensitivity analysis were performed. The first one consists of operating electric boiler and heat pump by electricity produced using natural gas instead of coal, however, results show that the gas boiler remained the most environmentally friendly. The second scenario assumed neglecting environmental impacts of transmission lines, transformers, and distribution lines, while retaining coal as a source of electricity production. Results show that the impacts of transmission lines and transformers are significant, but again, the gas-fired boiler remains the most environmental friendly.

تقارن هذه الدراسة بين ثلاثة أنظمة تسخين مياه مقترحة لنادي صحي متوسط الحجم في مدينة نابلس في فلسطين . ولكونها الأكثر استخداما في الأسواق المحلية فقد تم اعتماد مرجل الكهرباء ومرجل الغاز والمضخة الحرارية لدراستها. وكنقطة مرجعية في اختيار الحجم المناسب من كل نظام فقد تم الاعتماد على الاستهلاك اليومي من المياه الساخن على درجة الحرارة المناسبة والذي قدر بمعدل ٨ متر مكعب من الماء على درجة حرارة ٤٣ مئوية. ولتقييم الأثار البيئة المترتبة على دورة حياة هذه الأنظمة فقد استخدم اسلوب مركز العلوم البيئية في جامعة ليدن، حيث يتم تقسيم الأثار البيئية المترتبة إلى ١٠ أثار رئيسية. تطرقت الدراسة كذلك إلى التكلفة الإجمالية لكل نظام على اعتبار أن نسبة العائد هي ١٠٪ . الدراسة بينت أن المضخة الحرارية هي الاقل استهلاكا للطاقة بينما يحل مرجل الغاز، بينما كان مرجل الكهرباء الأكثر استهلاكا. ومن جهة التكاليف وبالنظر إلي التكاليف الانشائية والتشغيلية للانظمة الثلاث، فقد اشارت النتائج إلى أن المضخة الحرارية هي الأقل تكلفة خلال فترة حياتها بواقع ١٠٤،٦٨٣ دولر امريكي ، بينما حل مرجل الغاز ثانيا بواقع ١٦٧،٤٢٨ دولر امريكي ، أما مرجل الكهرباء فقد كان الأعلى تكلفة بواقع ٢٤٦،٤٣٣ دولر أمريكي. أما من ناحية الأثار البيئية المترتبة فقد كان هناك نوع من الإختلاف ، حيث أظهرت النتائج أن مرجل الغاز هو الأقل أثر على البيئة ، بينما تحل المضخة الحرارية ثانيا ، ومرجل الغاز ثالثا. في نهاية الدراسة تم تطبيق اثنين من السيناريوهات لاختبار حساسية الأنظمة تجاه الظروف التشغيلية المختلفة. ففي أول حال تم افتراض أن الكهرباء المستعملة لتشغيل مرجل الكهرباء والمضخة الحرارية تم انتاجها بواسطة محطة توليد تعمل بالغاز الطبيعي عوضا عن الفحم ، كان هناك تحسن في المؤشرات البيئية ، لكن بقي مرجل الغاز هو الافضل من ناحية الأثر البيئي. وفي الحالة الثانية تم استبعاد الأثر البيئي المترتب على خطوط النقل والتوزيع والمحولات. نتائج المؤشرات البيئة للمضخة الحرارية ومرجل الكهرباء تحسنت بشكل كبير وملحوظ ، لكن هذا لم يغير في حقيقة أن مرجل الغاز بقي الأكثر صداقة للبيئة حتى تحت هذه الظروف.
تقييم دورة حياة أنظمة تسخين المياه لاستعمالات نادي رياضي